Single Cell Transcriptomes Derived from Human Cervical and Uterine Tissue during Pregnancy. Issue 11 (15th May 2019) - Koh, Winston; Wu, Angela; Penland, Lolita; Treutlein, Barbara; Neff, Norma F.; Mantalas, Gary L.; Blumenfeld, Yair J.; El‐Sayed, Yasser Y.; Stevenson, David K.; Shaw, Gary M.; Quake, Stephen R.
Abstract: This work presents the workflow for generating single cell transcriptomes derived from primary human uterine and cervical tissue obtained during planned cesarean hysterectomies. In total, a catalogue of 310 single cell transcriptomes are obtained, cell types present in these biopsies are inferred, and specific genes defining each of the cellular types present in the tissue are identified. Further validation of the inferred cell identity is also demonstrated via meta‐analysis of independent repositories in literature generated by bulk sequenced data of fluorescence‐activated cell sorting sorted cells. Abstract : Single cell RNA‐seq performed on primary human uterine and cervical tissues reveals gene specific to cell types and corroborates expression data obtained from bulk sequencing studies.